Pendidikan Islam Berwawasan Multikultural Di Pondok Pesantren (Studi Etnografi di Kabupaten Kediri) - Binti Muliati (Institut Studi Islam Muhammadiyah (ISIMU) Pacitan, 2017)
The discussion about multicultural education is never finished. Multicultural education is as part of practical education strategy which have been developed in Indonesia since the reformation era. Multicultural education is important to be implemented in Indonesia because Indonesia students have a socio-cultural background that is different. One of institutions in Indonesia intensively implementing multicultural education is Islamic boarding school. This article is trying to explore the implementation of multicultural education with an ethnographic approach. Pesantren since the early days of teaching have instilled co-existence peacefully and recognizes equal rights, awarness, mutual learning and understanding, respect and appreciation for others so that found multicultural awareness on self-generation of Indonesia Moslem.